PERAN MEDIA SOSIAL DALAM STRATEGI PEMASARAN UNTUK MENINGKATKAN DAYA SAING USAHA RENTAL OUTDOOR DI MAGETAN - Setia Maharani; TATIK MULYATI; MUHAMMAD IMRON (ITB AAS Indonesia Surakarta, 2026)
This study aims to: 1) determine the role of social media in Van Adventure Magetan's marketing strategy; 2) determine how social media is utilized to increase the competitiveness of Van Adventure Magetan's outdoor rental business; 3) determine the obstacles faced in using social media as a marketing tool; 4) determine the efforts made by Van Adventure Magetan in optimizing social media to increase business competitiveness. The research method used is a qualitative research method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. Informants in this study consisted of business owners, employees, and customers of Van Adventure Magetan. Data analysis techniques used data reduction, data presentation, and drawing conclusions. The results of the study indicate that social media has an important role in Van Adventure Magetan's marketing strategy. Social media is used as a means of product promotion, delivering rental service information, communicating with customers, and building consumer trust through testimonials and documentation of customer activities. The use of social media has been proven to expand market reach, increase customer interest, and strengthen business competitiveness amidst the competition in the outdoor rental business. Obstacles faced include limited time in content management, competition from similar businesses, and rapid changes in digital trends. The conclusion of this study indicates that social media plays an effective role as a marketing strategy in increasing Van Adventure Magetan's competitiveness. Therefore, Van Adventure Magetan needs to improve content creativity, promotional consistency, and service quality to maintain and enhance its competitiveness.